The Effectiveness of Using Kinect-Based Dyslexia Therapy in Improving Reading Ability in Dyslexic Children: A Linguistic Study - Tammasse Tammasse; Jumraini Tammasse; Iin Fadhilah Utami; Fakhriawan Fathu Rahman (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Dyslexia is a learning disorder characterized by difficult in reading, writing, or spelling. People especially children with dyslexia have difficult to identify spoken words and converting them into letters or sentences. The aims of this study are 1) to find out the early symptoms of dyslexia in children, 2) to reveal the effectiveness of using video game media (kinect-based dyslexia therapy media) in improving reading skills in dyslexic children. This research used quantitative method. This research is an experimental longitudinal because there is an intensive observation of the subject within a certain period of time. The result of this study is to reduce the dyslexia children as much as possible to read by using the intervention “Kinect-Based Dyslexia Therapy” (LexiPal). Strong evidence of the success of the LexiPal intervention can be seen through the experimental method (calculated the difference in the position of the treatment group and the control group at the end of the experiment). Calculations are carried out through simple statistical calculations.